Knowledge, attitude, perception and practices towards disposal of sanitary napkins among young females: A cross-sectional study - Vivekanand Kattimani; Donipudi Lakshmi Durga Alekhya; Sahithi Pathralapati; Shilpa Susan Sojin; Shikha Patel; Chinmayi Prabhakar; Heena Dixit (Wolters Kluwer Medknow Publications, 2024)
Background: Almost 70% of women residing in urban areas and 48% of women in rural areas use sanitary napkins in India. According to menstrual health alliance India (MHAI), single sanitary pad will take about 500-800 years to decompose as the plastic used in manufacturing is nonbiodegradable and causes severe noxious effects contributing to global warming through the production of planet warming fuels which eventually have severe impact on environment sustainability. Hence, the study was undertaken to contribute the evidence for the "Clean and Green India". Aim: To know the perception and practice of disposal of sanitary napkins among young college-going females in India. Materials and Methods: A cross-sectional study was conducted throughout the country employing a self-administered questionnaire using a survey link sent through social media. Data collected were analyzed and interpreted using SPSS version 20.0. Result: The study population comprised 484 young college girls with a mean age of 20.92 ± 1.86 years and 96.9% of them are using sanitary napkins as menstrual absorbent aids. The most common method employed for the disposal of sanitary napkins was dumping them in the bin (87.4%). About 63.2% of them had no knowledge about sanitary napkin-burning machines. Around 92% think that improper disposal of sanitary napkins can cause health problems. Conclusion: The findings from the study revealed that a significant number of women were practicing noneco-friendly disposal methods and menstrual hygiene aids which are a bane to the ecosystem. Study warrants the education and training of females to achieve a green and clean sustainable India.